2018
DOI: 10.1073/pnas.1805007115
|View full text |Cite
|
Sign up to set email alerts
|

Grid-like hexadirectional modulation of human entorhinal theta oscillations

Abstract: The entorhinal cortex contains a network of grid cells that play a fundamental part in the brain’s spatial system, supporting tasks such as path integration and spatial memory. In rodents, grid cells are thought to rely on network theta oscillations, but such signals are not evident in all species, challenging our understanding of the physiological basis of the grid network. We analyzed intracranial recordings from neurosurgical patients during virtual navigation to identify oscillatory characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 35 publications
(46 reference statements)
2
64
1
Order By: Relevance
“…The idea of a 2-D semantic-temporal space suggests that other signatures of 2-D spatial navigation, such as hexadirectional modulation of neural activity, may also be detectable during episodic recall. Two groups recently showed that theta power in the human entorhinal cortex is hexadirectionally modulated during virtual navigation [58,59]. In the fMRI literature, it has been shown that hippocampal activity encodes for spatial [60] and abstract representational distances [61], and that hexadirectional modulation of the BOLD signal is observed during mental travel through abstract or imagined spaces [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The idea of a 2-D semantic-temporal space suggests that other signatures of 2-D spatial navigation, such as hexadirectional modulation of neural activity, may also be detectable during episodic recall. Two groups recently showed that theta power in the human entorhinal cortex is hexadirectionally modulated during virtual navigation [58,59]. In the fMRI literature, it has been shown that hippocampal activity encodes for spatial [60] and abstract representational distances [61], and that hexadirectional modulation of the BOLD signal is observed during mental travel through abstract or imagined spaces [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…After having established a relationship between theta oscillations and spatial memory, we sought to examine whether theta power exhibited hexagonal modulation with respect to the participants' head direction during walking. This effect is thought to resemble the grid cell system for navigation in rodents and has been observed in stationary human participants performing stationary 2-D virtual navigation 13,14,24,25 (Fig. 4a, b; Methods), however, has not yet been explored in freely moving humans navigating a real environment.…”
Section: Mainmentioning
confidence: 78%
“…We employed methods that were previously applied to fMRI data from immobile participants 15 and were recently adapted to human iEEG data also in immobile participants who completed a view-based 2-D VR spatial navigation task 13,14 . First, we computed the allocentric head-direction of the participant (defined as the orientation of the rigid body tracked with the motion capture system) with respect to the physical room.…”
Section: Hexadirectional Modulation Of Theta Powermentioning
confidence: 99%
“…We developed AR and VR paradigms that adapted the "Treasure Hunt" spatial memory task, previously used in [17,18,20,31]. Treasure Hunt is an object-location associative memory task in which subjects are asked to remember the locations of various hidden objects in a virtual environment.…”
Section: Methodsmentioning
confidence: 99%